Perlindungan Hak Isteri Dalam Pentadbiran Undang-Undang Perceraian Di Mahkamah Syariah Selangor Dan Wilayah Persekutuan Kuala Lumpur - Abdul Samat Musa; Abdul Manan Ismail; Dina Imam Supaat; Arif Fahmi Md Yusof (Universiti Sains Islam Malaysia, 2024)
This research focuses on legal aspects related to divorce particularly pertaining to rights of women as administered in the Syariah Courts of Selangor and Federal Territory of Kuala Lumpur. It pays special attenti011 to legal aspects and the syariah law in protection of women's rights in the administration of divorce laws and its implementation and enforcement, regulations at the pre-trial level, during the trial and the implementation of court's decision and enforcement of court order. The research is library and field based. For field research the researcher conducted survey involving husband and wives who were directly concerned with divorce cases, legal practitioners, those officers who are involved in the pre-trial level. One of our major finding is that the law related to divorce has provided sufficient and fair protection for women but there are certain matters and aspects of the implementdion that need improvement.